Capturing activated neurons and synapses. (March 2020) - Choi, Jung-Eun; Kim, Jiwon; Kim, Jinhyun
Highlights: Advances in IEG-based gene expression system in response to neural activity enabled access to activated neuronal ensemble. Photoactivatable gene expression system in response to neural activity also had great advances recently. Advances in active synapse labeling system allow capturing of activated synapses. New approaches for manipulation of activated synapses have been developed. Abstract: An important yet very challenging goal of neuroscience is to understand how brain activity drives cognition and behavior. Many useful tools have been developed to study neurons and synapses, the fundamental units of brain activity. Here, we review recently developed methods to visualize and manipulate active neurons and synapses, providing useful and compelling information about functional neuronal circuitry.